The Quotient Ring by an Ideal of a Ring of Some Matrices is Isomorphic to $\Q$.
Problem 525
Let
\[R=\left\{\, \begin{bmatrix}
a & b\\
0& a
\end{bmatrix} \quad \middle | \quad a, b\in \Q \,\right\}.\]
Then the usual matrix addition and multiplication make $R$ an ring.
Let
\[J=\left\{\, \begin{bmatrix}
0 & b\\
0& 0
\end{bmatrix} \quad \middle | \quad b \in \Q \,\right\}\]
be a subset of the ring $R$.
(a) Prove that the subset $J$ is an ideal of the ring $R$.
(b) Prove that the quotient ring $R/J$ is isomorphic to $\Q$.
Sponsored Links
Contents
Proof.
(a) Prove that the subset $J$ is an ideal of the ring $R$.
Let
\[\alpha=\begin{bmatrix}
0 & a\\
0& 0
\end{bmatrix} \text{ and } \beta=\begin{bmatrix}
0 & b\\
0& 0
\end{bmatrix}\]
be arbitrary elements in $J$ with $a, b\in \Q$.
Then since we have
\begin{align*}
\alpha-\beta=\begin{bmatrix}
0 & a-b\\
0& 0
\end{bmatrix}\in J,
\end{align*}
the subset $J$ is an additive group.
Now consider any elements
\[\rho=\begin{bmatrix}
a & b\\
0& a
\end{bmatrix} \in R \text{ and } \gamma=\begin{bmatrix}
0 & c\\
0& 0
\end{bmatrix}\in J.\]
Then we have
\begin{align*}
\rho \gamma&=\begin{bmatrix}
0 & ac\\
0& 0
\end{bmatrix}\in J \text{ and }\\[6pt]
\gamma \rho &=\begin{bmatrix}
0 & ca\\
0& 0
\end{bmatrix}\in J.
\end{align*}
Thus, each element of $J$ multiplied by an element of $R$ is still in $J$.
Hence $J$ is an ideal of the ring $R$.
(b) Prove that the quotient ring $R/J$ is isomorphic to $\Q$.
Consider the map $\phi:R\to \Q$ defined by
\[\phi\left(\, \begin{bmatrix}
a & b\\
0& a
\end{bmatrix} \,\right)=a,\]
for $\begin{bmatrix}
a & b\\
0& a
\end{bmatrix}\in R$.
We first show that the map $\phi$ is a ring homomorphism.
First of all, we have
\begin{align*}
\phi\left(\, \begin{bmatrix}
1 & 0\\
0& 1
\end{bmatrix} \,\right)=1.
\end{align*}
Thus $\phi$ maps the unity element of $R$ to the unity element of $\Q$.
Take
\[\begin{bmatrix}
a & b\\
0& a
\end{bmatrix}, \begin{bmatrix}
c & d\\
0& c
\end{bmatrix}\in R.\]
Then we have
\begin{align*}
\phi\left(\, \begin{bmatrix}
a & b\\
0& a
\end{bmatrix}+\begin{bmatrix}
c & d\\
0& c
\end{bmatrix} \,\right)&=\phi\left(\, \begin{bmatrix}
a+c & b+d\\
0& a+c
\end{bmatrix} \,\right)=a+c\\[6pt]
&=\phi\left(\, \begin{bmatrix}
a & b\\
0& a
\end{bmatrix} \,\right)+\phi\left(\, \begin{bmatrix}
c & d\\
0& c
\end{bmatrix} \,\right)
\end{align*}
and
\begin{align*}
\phi\left(\, \begin{bmatrix}
a & b\\
0& a
\end{bmatrix}\begin{bmatrix}
c & d\\
0& c
\end{bmatrix} \,\right)&=\phi\left(\, \begin{bmatrix}
ac & ad+bc\\
0& ac
\end{bmatrix} \,\right)=ac\\[6pt]
&=\phi\left(\, \begin{bmatrix}
a & b\\
0& a
\end{bmatrix} \,\right)\phi\left(\, \begin{bmatrix}
c & d\\
0& c
\end{bmatrix} \,\right).
\end{align*}
It follows from these computations that $\phi:R\to \Q$ is a ring homomorphism.
Next, we determine the kernel of $\phi$.
We claim that $\ker(\phi)=J$.
If $\rho=\begin{bmatrix}
a & b\\
0& a
\end{bmatrix}\in \ker(\phi)$, then we have
\[0=\phi(\rho)=\phi\left(\, \begin{bmatrix}
a & b\\
0& a
\end{bmatrix} \,\right)=a.\]
So $\rho=\begin{bmatrix}
0 & b\\
0& 0
\end{bmatrix}\in J$, and hence $\ker(\phi)\subset J$.
On the other hand, if $\rho=\begin{bmatrix}
0 & b\\
0& 0
\end{bmatrix}\in J$, then it follows from the definition of $\phi$ that $\phi(\rho)=0$.
Thus, $J \subset \ker(\phi)$.
Putting these two inclusions together yields $J=\ker(\phi)$.
Observe that the homomorphism $\phi$ is surjective.
In fact, for any $a\in \Q$, we take $\begin{bmatrix}
a & 0\\
0& a
\end{bmatrix}\in R$. Then we have
\[\phi\left(\, \begin{bmatrix}
a & 0\\
0& a
\end{bmatrix} \,\right)=a.\]
In summary, $\phi:R\to \Q$ is a surjective homomorphism with kernel $J$.
It follows from the isomorphism theorem that
\[R/J\cong \Q,\]
as required.
Remark.
Recall that the kernel of a ring homomorphism $\phi:R\to S$ is always an ideal of $R$.
Thus, the proof of (b) shows that $J$ is an ideal of $R$. This gives an alternative proof of part (a).
Add to solve later
Sponsored Links